Shaking-Table Test on a Multi-Story Continuous Vibration-Control System Employing Pulley Amplification Mechanism - Majima, Ryo; Yamasaki, Yasuo; Saito, Taiki (Salehan Institute of Higher Education, 2025)
This study proposes an innovative passive vibration-control system, named the Pulley Damper Multi-story System (PDMAS), which incorporates pulley tackles installed at multiple stories in the successive stories to amplify inter-story displacement. This configuration significantly enhances the energy absorption efficiency of the linked dampers at the middle of the cable by utilizing the cumulatively amplified story displacements via a continuously stretched cable across the entire structure. The proposed system shows notable potential for controlling responses induced by higher vibration modes by customizing the wire installation layout. The aim of this study is to introduce PDMAS and to investigate its seismic-mitigation effectiveness. As a primary investigation of this new system, comparative experimental studies were conducted through shaking-table tests on nine specimens featuring various cable layouts optimized for the first and second structural vibration modes, with or without dampers, under harmonic waves, white-noise waves, and simulated seismic waves. The experimental results demonstrate that the PDMAS effectively accommodates the cumulative amplified story displacement across the structure to match theoretical damper values. Furthermore, the specimens employing PDMAS with a wire layout optimized for the first structural mode reduced both acceleration and displacement by nearly half compared to specimens without PDMAS. Doi: 10.28991/CEJ-2025-011-01-02 Full Text: PDF